(untitled) (RuMoRes, 2008)
Some brazilian researchers have been tracing, more expressively in the last years, the profile of the journalism research in Brazil. The approaches have a broad aim, with subject survey, technological support and research lines. I would like to start from these conjunct of works proposed in macro-analysis to question, specifically, methodological options in journalism studies that take as basis newspaper articles.